Gender difference in the association between composite dietary antioxidant index and all-cause mortality - Duan, Lanzhi; Zeng, Rui; Wang, Jiang; Hu, Sisi; Wang, Weiye (Frontiers in Nutrition, 2025)
BackgroundExisting studies on the association between the composite dietary antioxidant index (CDAI) and all-cause mortality are controversial. We aimed to analyze the association of CDAI with all-cause mortality, and determine the influence of gender on this association.MethodsThe data of adult participants (age ≥ 18) from the National Health and Nutrition Examination Survey (NHANES) cycles spanning 2001 to 2018 were analyzed. The NHANES-issued identifiers for participants enabled the linkage of data from the NHANES Public Use Linked Mortality File.ResultsThe study encompassed a sample of 15,651 individuals. The mean CDAI was 0.52 ± 6.06. The restricted cubic spline revealed that the hazard ratio (HR) of all-cause mortality decreased significantly with increasing CDAI. However, this negative association existed only when the CDAI was less than 5. Multivariate Cox regression analysis showed that compared to the first CDAI quartile, the HR of all-cause mortality was significantly decreased in the third and fourth quartiles (both p < 0.001), and the p-value of the trend test was <0.001. In the subgroup analysis, a notably strong negative association between CDAI and the risk of all-cause mortality was only observed in men (p for interaction <0.001).ConclusionHigher CDAI is associated with a reduced risk of all-cause mortality exclusively in adult males, underscoring the substantial influence of gender on this relationship.